IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP HASIL BELAJAR PESERTA DIDIK - Faizah, Hanun (Universitas Negeri Surabaya, 2025)
One of the obstacles in the science learning process is the use of teaching models that still focus on the teacher, resulting in students not being actively involved. This leads to low learning outcomes for students in science education. This study aims to determine the effectiveness of the cooperative learning model of the talking stick type in improving student learning outcomes. The research method employs a quantitative approach with a pre-experimental design, specifically a one-group pre-test post-test design conducted at Mts Sunan Kalijaga Surabaya. The sample for this study was taken using cluster random sampling techniques because the samples encountered were homogeneous, showing no differences in the academic grouping of students. The instruments used include observation sheets for implementing the model and test questions to measure student learning outcomes. The data analysis techniques used include prerequisite analysis tests using validity tests of observation sheets and tests through expert judgment, normality tests, hypothesis tests, and N-Gain tests. The normality test utilized Shapiro-Wilk, and the hypothesis test employed a paired sample t-test using SPSS 25 for Windows with a significance level of >0.05. Overall, the results indicate an improvement in learning outcomes with the application of the cooperative learning model of the talking stick type, with specific values showing an average pretest score of 50.27 and an average posttest score of 83.16. The results of the normality test analysis for student learning outcomes showed a significance value of 0.074 for pretest scores, while the posttest scores had a significance value of 0.108, indicating that the data is normally distributed since it is >0.05. With a paired sample t-test value of 0.000 and an average N-Gain score of 0.582 indicating a moderate improvement, the average observation score for the implementation of the talking stick cooperative learning model was 26 with a percentage of 88.6%, indicating a very effective criterion. These data show that the cooperative learning model of the talking stick type is effective in improving student learning outcomes.